ANALISA PENGEMBANGAN SUMBER DAYA MANUSIA SEBAGAI UPAYA PENINGKATAN KINERJA KSPPS ASSYAFI’IYAH METRO-LAMPUNG - Santoso, Haris; Rahmawati, Rita; Khotamin, Nur Alfi (Islamic Economics Program, Faculty of Islamic Economics and Business, 2020)
Human resource development is considered to be one of the most effective ways to improve company performance and productivity. With the development of human resources, it is hoped that the technical skills and professional skills of employees can be improved. However, the success of the program implementation cannot be carried out immediately during implementation, but can be seen from the results of the employees' work after participating in human resource development whether there have been changes or not. Based on the results of research and discussion related to this research, the authors conclude that: BMT Assyafi'iyah Metro Lampung City in improving employee performance is through human resource development, namely by means of transfer, promotion, supervision, work motivation and coaching. career. Human resource development carried out by BMT Assyafi'iyah Metro Lampung City can improve employee performance. The provision of career coaching has an impact on the increasing work performance of employees, this is evident from the provision of internships and training. Supervision has an impact on employees so that employees are more honest in carrying out their duties. So that it is hoped that there will be no deviations by employees. And also the employees are more disciplined in various ways, one of which is the punctuality and accuracy of the targets given. Granting a job transfer has an impact on employees so that they become more responsible for the tasks that have been assigned to these employees.